Entre sambas e rezas: vivências, negociações e ressignificações da cultura afro-brasileira no Bexiga - Nascimento, Larissa Aparecida Camargo do (2014)
In the late nineteenth century there was formed the Quilombo Saracura in Bexiga. Later there was an intense process of territorial / racial redefinition which promoted the shift of the black downtown area of São Paulo to Bexiga. This stream was concomitant with the arrival of Italian immigrants in the neighborhood. The black population lives in this area until the present day, but different medias represents the Bexiga as a typically Italian region in Sao Paulo, erasing the contributions from other social groups. Given the process of racialization and asymmetrical relations, this research presents as general purpose to investigate how the black culture in the neighborhood are interpreted by self-declared black subjects. For this, was researched a samba school, a Candomblé and a black pastoral that marks this urban context. Besides the direct observation, were realized interviews based in the history of life. Given that the culture undergoes transformations and that identity is not fixed, was analysed the translation, ressignification and/or tensions between different cultures and identities. The research is based on theorists of Cultural Studies, especially authors who works from a Postcolonial Perspective.